Special issue "Adductomics - Pereira, Sofia A. (2019)
Adductomics studies represent effective tools for better understand how exposure to exogenous and endogenous reactive chemical agents underlie mechanism of diseases. This special issue is focused not only on summarizing the analytical methodologies used for DNA, protein, and mercapturic acid adductomics tools but also on highlighting the opportunities and challenges for the application of this type of studies in biomedical research.